2016
DOI: 10.14238/pi44.2.2004.46-50
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic profile in pediatric wards, Department of Child Health, Cipto Mangunkusumo Hospital

Abstract: Introduction The medical profession has currently come to a con-clusion that the major problem in the future is failure of treatmentdue to antibiotic-resistant microorganisms.Objective The aim of this study was to determine the profile ofantibiotics used in the Pediatric Wards of Department of Child Health,Medical School, University of Indonesia, Cipto Mangunkusumo Hos-pital, Jakarta.Methods A descriptive retrospective study was conducted on all pa-tients hospitalized in the Pediatric Wards of Department of Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
3
1
Order By: Relevance
“…6 This study was also comparable with the study done in Indonesian pediatric wards where the greatest user of antibiotics was the age group of 1 to 5 years old. 18 Apart from the present finding, Warrier et al also reported that ampicillin and cefotaxime had the highest exposure rates in neonatal intensive care units. 22 For patients receiving ampicillin, the concurrent use of cefotaxime during the first 3 days after birth either is a surrogate for an unrecognized factor or is itself associated with an increased risk of death, compared with the concurrent use of gentamicin.…”
Section: Discussioncontrasting
confidence: 43%
See 2 more Smart Citations
“…6 This study was also comparable with the study done in Indonesian pediatric wards where the greatest user of antibiotics was the age group of 1 to 5 years old. 18 Apart from the present finding, Warrier et al also reported that ampicillin and cefotaxime had the highest exposure rates in neonatal intensive care units. 22 For patients receiving ampicillin, the concurrent use of cefotaxime during the first 3 days after birth either is a surrogate for an unrecognized factor or is itself associated with an increased risk of death, compared with the concurrent use of gentamicin.…”
Section: Discussioncontrasting
confidence: 43%
“…21 Besides, a study done in the pediatric ward of Cipto Mangunkusumo Hospital, Indonesia, explored that the most frequently prescribed multiple antimicrobials were ampicillin + chloramphenicol, cefotaxime + amikacin, cefotaxime + cotrimoxazole, and cefotaxime + RHZE. 18 Regarding specific age groups, this study showed that ampicillin and gentamicin were commonly prescribed for children below 5 years and had been the predominant antimicrobial therapy in neonates, whereas ceftriaxone and crystalline penicillin were prescribed predominately to infants and children with the age group of 1 to 5 years. This result supports a study carried out in ARH where ampicillin and gentamicin were frequently prescribed to the age group of less than 1 year; however, ceftriaxone was primarily prescribed to children with the age group of greater than 5 years.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Age groups are divided into five groups: less than one year (35.5%), 1-3 years (28.25%), 4-6 years (17.25%), 7-9 years (10%) and 10-12 years (9%). (Husni et al,2004). In this study, and as mentioned in (Yek et al, 2010).…”
Section: Methodsmentioning
confidence: 55%